2014
DOI: 10.1152/ajprenal.00518.2013
|View full text |Cite
|
Sign up to set email alerts
|

Increase in SGLT1-mediated transport explains renal glucose reabsorption during genetic and pharmacological SGLT2 inhibition in euglycemia

Abstract: .-In the kidney, the sodiumglucose cotransporters SGLT2 and SGLT1 are thought to account for Ͼ90 and ϳ3% of fractional glucose reabsorption (FGR), respectively. However, euglycemic humans treated with an SGLT2 inhibitor maintain an FGR of 40 -50%, mimicking values in Sglt2 knockout mice. Here, we show that oral gavage with a selective SGLT2 inhibitor (SGLT2-I) dose dependently increased urinary glucose excretion (UGE) in wild-type (WT) mice. The dose-response curve was shifted leftward and the maximum response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
238
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(262 citation statements)
references
References 20 publications
23
238
0
1
Order By: Relevance
“…While this result was surprising and cannot be explained, a previous study (4) has also demonstrated differential expression of SGLT1 mRNA and protein. From these results, we interpret that diabetic BTBR ob/ob mice do not show a mechanism of compensatory increased SGLT1-mediated glucose reabsorption under complete SGLT2 blockade, as has been demonstrated by Vallon and coworkers in C57Bl/6 mice (25).…”
Section: Mesangial Index Fraction [%]supporting
confidence: 78%
“…While this result was surprising and cannot be explained, a previous study (4) has also demonstrated differential expression of SGLT1 mRNA and protein. From these results, we interpret that diabetic BTBR ob/ob mice do not show a mechanism of compensatory increased SGLT1-mediated glucose reabsorption under complete SGLT2 blockade, as has been demonstrated by Vallon and coworkers in C57Bl/6 mice (25).…”
Section: Mesangial Index Fraction [%]supporting
confidence: 78%
“…10 cannot claim to be secure in estimating the glycosuric effect of SGLT2 inhibitors. Nevertheless, Rieg et al (61) reported that with chronic empagliflozin administration to mice, fractional glucose reabsorption was about 45-50%. With reference to the calculations of this model (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 These inhibitors may also decrease insulin secretion with blood glucose levels that remain close to the normal range due to the blockade of glucose reabsorption at the renal proximal tubule. 2 Problems have emerged with the use of SGLT2 inhibitors, some of which might have arisen directly from their high level of efficiency.…”
Section: Introductionmentioning
confidence: 99%